Conceptualising Stakeholder Commitment, Closed-Loop Supply Chains and Organisational Performance: A Circular Economy Perspective - Johari, Nor Azila Mohd; Mokhtar, Ahmad Rais Mohamad; Sayuti, Nazura Mohamed (Journal of Entrepreneurship, Business and Economics, 2022)
In the supply chain context, circular economy (CE) initiatives strive to minimise waste and pollution by promoting remanufacturing to reduce the reliance on virgin materials. To realise the CE, closed-loop supply chains (CLSCs) have been identified as the backbone of its implementation. Unfortunately, little attention has been paid to exploring the contribution of CLSC practices in manufacturing industries, particularly towards the transition to a more circular economy in emerging economies. This study aims to propose a conceptual framework for examining the impact of stakeholders’ commitment on CLSCs and organisational performance. In general, this study proposes that stakeholders’ commitment (customers’ pressure, top management commitment, buying firms’ leadership, and government support) has a significant impact on CLSCs implementation. Furthermore, this study also proposes that CLSCs implementation contributes significantly towards organisational performance. This study suggests that future studies should conduct an empirical investigation using the conceptual framework of this paper. It is expected that this study will facilitate discussions on the need to deepen the comprehension of stakeholders’ commitment and its influence on CLSCs and organisational performance. The study contributes to the existing literature by addressing the gaps between stakeholders’ commitment, CLSCs, and organisational performance in realising the transition towards CE. Research paper Keywords: Circular economy, closed-loop, supply chain, reverse logistic, stakeholder, sustainability Reference to this paper should be made as follows: Johari, N. A. M., Mokhtar, A. R. M., & Sayuti, N. M. (2022). Conceptualising Stakeholder Commitment, Closed-Loop Supply Chains and Organisational Performance: A Circular Economy Perspective. Journal of Entrepreneurship, Business and Economics , 10 (2S2), 109–137.